Partial Purification and Characterization of Glutathione S-Transferase from the Livers of Malaysian Catfish (Clarias Batrachus) and Malaysian Red Tilapia (Oreochromis Sp.) - Chin, Chee Meng (2005)
The present study is concerned mainly with partial purification and characterization of cytosolic GST from livers of Malaysian catfish and Malaysian red tilapia as both species are of economic and commercial importance in Malaysia being the major freshwater fishes consumed. This study hopes to establish the patterns of cytosolic glutathione S-transferase isoenzymes in the catfish and red tilapia. This may be useful to further achieve an understanding toward this enzyme in view of using it as a tool in environmental monitoring. The hepatic GST enzyme from catfish and red tilapia was partially purified 15X and 27X respectively in comparison to the ultra-centrifuged cytosolic fraction by affinity chromatography. Specific GST activity of 12.69 unitlmg protein and 33.42 unitlmg protein was obtained from livers of catfish and red tilapia using l-chloro- 2,4-dinitrobenzene (CDNB) as a substrate. Isolation of GST isoenzymes from affinity purified fractions was achieved by preparative isoelectric-focusing. Two isoenzymes; one major isoenzyme designated Cil and one minor isoenzyme designated Ci2 were isolated from catfish liver with an apparent pl of 6.20 and 8.73 respectively. One isoenzyme designated Ti1 was isolated from red tilapia liver with an apparent pi of 9.14. SDS-PAGE analysis suggests that the isolated isoenzymes appear to be homodimeric in nature with subunit molecular weight of 29.7 21.7 kDa (Cil), 27.7 21.3 kDa (Ci2) and 29.9 +0.9 kDa (Til). As has been found for most GSTs, highest catalytic activity was obtained with CDNB. With the exception of the isoenzyme from cytosol and affinity purified fractions of red tilapia, none of the catfish fractions displayed enzyme activities towards 1,2- dichloro-4-nitrobenzene (DCNB) and ethacrynic acid (EA). Therefore, both catfish and tilapia possess hepatic glutathione S-transferase activity, indicating that they are capable of conjugating endogenous or xenobiotic metabolites/compounds as a result of foreign exposure or oxidative metabolism with glutathione, thereby making it a useful tool as a effective biomarker of aquatic contamination.